2018
DOI: 10.1002/ar.23834
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Behavior Analysis of Muscle Cells under IFN‐γ Stimulation in Vitro and in Vivo

Abstract: Muscle cells could serve as antigen-presenting cells, and participate in the activation of immune response. Immunological characteristics of muscle cells, and their capacities to equip themselves with immunorelevant molecules, remain to be elucidated. In this study, we investigated the immunological properties of myoblasts and differentiated myotubes in vitro and in vivo, under the IFN-γ induced inflammatory condition. We found that the fused C C myotubes are more sensitive to inflammatory stimulation, and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
(65 reference statements)
3
25
1
1
Order By: Relevance
“…Consistently, knock-down of NLRP3 abrogated the promoting effects of cisplatin-DB combined treatment on cell apoptosis in CR-GC cells, which were in accordance with the previous studies [38,40,41]. Furthermore, the intrinsic PD-L1/NLRP3 pathway had been reported in the previous studies [31] [32], and we validated that low-dose DB inhibited PD-L1 expressions to activate NLRP3 mediated cell pyroptosis in cisplatin treated CR-GC cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently, knock-down of NLRP3 abrogated the promoting effects of cisplatin-DB combined treatment on cell apoptosis in CR-GC cells, which were in accordance with the previous studies [38,40,41]. Furthermore, the intrinsic PD-L1/NLRP3 pathway had been reported in the previous studies [31] [32], and we validated that low-dose DB inhibited PD-L1 expressions to activate NLRP3 mediated cell pyroptosis in cisplatin treated CR-GC cells.…”
Section: Discussionsupporting
confidence: 92%
“…For example, myeloid phosphate and tension homology deleted on chromosome ten (PTEN) promoted chemotherapy-induced NLRP3 mediated cell pyroptosis to inhibit cancer development [30], and activation of NLRP3-mediated pyroptotic cell death enhanced the cytotoxic effects of cisplatin in non-small cell lung cancer (NSCLC) [29]. Of note, Bala et al validated that there existed an intrinsic PD-L1/NLRP3 signaling pathway in melanoma cells [31], and the correlations between PD-L1 and NLRP3 had also been observed in interferon-γ (IFN-γ) induced myotubes [32]. However, the detailed information for the PD-L1-NLRP3 pathway had not been deeply investigated in other types of cells, such as GC cells.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few reports of NLRP3 inflammasome activation in skeletal muscle cell. 47,48 Ding et al. reported NLRP3 inflammasome activation in interferon gamma (IFN-γ) treated C2C12 cultured myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…reported NLRP3 inflammasome activation in interferon gamma (IFN-γ) treated C2C12 cultured myotubes. 47 McBride et al. reported that NLRP3 inflammasome contributes to sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Myoblasts and myotubes can express a surprising variety of immunologically important molecules, including class I/II major histocompatibility complex (MHC-I/II) and co-stimulatory molecules in the presence of IFN-γ or other proinflammatory cytokines [47, 48]; this suggests that, under proinflammatory environment, muscle cells can actively participate in local immune reactions. We have demonstrated that estrogen signaling contributed to muscle inflammation response, which could reflect that estrogen signaling possibly affects on intrinsic immunological capacities of muscle cells, like it does for immune cells.…”
Section: Resultsmentioning
confidence: 99%